ANALISIS DAMPAK COVID-19 TERHADAP RETURN SAHAM (STUDI KASUS PADA PERUSAHAAN LQ-45) - Dita Dieni Khoirunisa; Afifudin Afifudin; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This research was conducted to analyze how the impact before and after the emergence of Covid-19 on the return of shares in LQ-45 companies. Samples from this study are companies included in Lq-45. Sampling in this study using purposive sampling techniques by setting several criteria. This research is focused on the window period of 3 days before and 3 days after the entry of Covid-19, namely on March 2, 2020. The paired sample t-test test was used as an analysis of the data of this study. From the research that has been done it is known that there is no impact resulting from the presence of Covid-19 it is known from the value of sig (2-tailed) of 0.644.where sig (2-tailed) > 0.05 then  accepted and rejected.Keywords: Covid-19, Return, Lq-45, Event study.